Islamic Banking Performance Analysis: Comparison in Turkey, Indonesia, and Malaysia - İlkay Aydoğmuş (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
The goal of this study is to evaluate and analyze the impact of Indonesian, Malaysian, and Turkish Islamic banking performance on the Capital Adequacy Ratio (CAR), the Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF). The Capital Adequacy Ratio (CAR), the Financing to Deposit Ratio (FDR), and the Non-Performing Financing (NPF) are independent variables in the quantitative study. The dependent variable, profitability (Y), will be analyzed using the panel data regression method (Eviews). Using a purposive sampling technique, the researchers processed the data from 187 annual reports of Islamic banking in Indonesia, Malaysia, and Turkey from 2008 to 2018. According to the study's findings, the financing to deposit ratio (X2) and then capital adequacy ratio (X1) partially influence for profitability variable (Y) in Indonesia, Malaysia, and Turkey, but not in Malaysia. Non-Performing Financing/NPF (X3) (Y) only marginally significantly impacted the profitability variable. The study's findings suggest that CAR, FDR, and NPF with variable profitability can enhance Islamic banking's performance in Indonesia, Malaysia Turkey